Redox status of professional soccer players is influenced by training load throughout a season - Le Moal, E.; Groussard, C.; Paillard, T.; Chaory, K.; Le Bris, R.; Plantet, K.; Pincemail, J.; Zouhal, H. (International Journal of Sports Medicine, 2016)
The purpose of this study was to follow-up the variation of pro-/antioxidant status throughout a whole season in elite professional soccer players from the French league (n=19, 18.3±0.6 years) and to examine a possible link between these variations and training load. 5 time points (T1, T2, T3, T4, T5) were proposed to surround crucial periods of training during the whole season: the pre-season training/mid-season periods (T1-T2 and T3-T4), the championship or in-season periods (T2-T3 and T4-T5). At these times, blood samples were collected to measure pro-/antioxidant status (in erythrocytes: the ratio of reduced glutathione/oxidized glutathione, superoxide dismutase and glutathione peroxidase activities, in plasma: alpha-tocopherol, beta-carotene), and dietary intakes were also recorded. Training loads were quantified by the rating of perceived exertion method weekly throughout the season. Pro-/antioxidant-related measurements showed no modifications except for GSH/GSSG ratio, which evolved significantly between season periods: from 36.43±4.15 (T1) to 115.99±16.43 (T2) to 91.64±21.24 (T3) to 202.29±29.26 (T4) to 59.61±14.61 (T5). We observed a significant correlation (r2=0.84) between changes in GSH/GSSH ratio and cumulated mean training loads. In conclusion, these results suggest that the redox status of professional soccer players is altered according to training period (in-season periods) and that GSH/GSSH ratio variations are correlated with cumulated training loads.